Smoking of health students State and Foundation University Example - AKYURT, NURAN (E D P SCIENCES, 2017)
The purpose of the study is to take a look at the smoking habits of the undergraduate students studying in the health programs of state and private universities, and to determine their opinion about the smoking ban. The research is a descriptive type study. The survey was conducted in February 2017. The participation rate in the survey is 75.5%. A questionnaire consisting of 23 questions was applied to the students. In the questionnaire, students were asked about their socio-demographic characteristics, the age at which they started smoking, in which situations they resort to cigarette, their opinion about addiction and on the implementation of the law Prevention and control of the harmful effects of tobacco products.
Keywords: Cigarettes; Smoking; Health Students; Law; Habit; CIGARETTE-SMOKING; SAUDI-ARABIA; TOBACCO USE; WATERPIPE TOBACCO; MEDICAL-STUDENTS; PARENTAL SMOKING; RISK-FACTORS; PREVALENCE; BEHAVIOR; ADOLESCENTS